Longitudinal Relations Between Child Maltreatment in Families and Psychological Maltreatment by Teachers: The Mediating Roles of Internalizing and Externalizing Problems Among Chinese Children - Gong, Xue (Journal of interpersonal violence, 2023)
Relationships in the family (e.g., child maltreatment in families) and school environments (e.g., psychological maltreatment by teachers) are influential in children’s socialization, but how family and teacher–student domains mutually affect each other and which mediating mechanisms are involved in cross-domain spillover at the within-person level are not well understood. This study examined the bidirectional relations between child maltreatment in families and psychological maltreatment by teachers and whether internalizing and externalizing problems functioned as mediators between them after separating between-person effects from within-person effects. A total of 4270 Chinese children (54.9% boys; Mage = 9.92; SD = 0.51) participated in a five-wave longitudinal study with 6-month intervals. Results from random intercept cross-lagged panel modeling mainly found that: (1) Child maltreatment in families predicted psychological maltreatment by teachers, and vice versa; (2) child maltreatment in families influenced psychological maltreatment by teachers through externalizing problems; child maltreatment in families affected the likelihood of psychological maltreatment by teachers via the sequential effect from internalizing problems to externalizing problems at the within-person level; and (3) internalizing and externalizing problems mediated the longitudinal relations from psychological maltreatment by teachers to child maltreatment in families separately. Findings demonstrated bidirectional spillover effects in the domains of family and teacher-student relationships, suggesting that children may be trapped in a vicious cycle of negative relationships through internalizing and externalizing problems, either directly or indirectly. Thus, these two domains influence each other through children’s internalizing and externalizing problems. Interventions aimed at addressing maltreatment should include family, school, and individual (i.e., internalizing and externalizing problems) components to prevent a downward spiral.